Analisis Faktor Gizi dan Konsumsi Makanan sebagai Prediktor Prestasi Belajar Anak Sekolah Dasar - Antun Rahmadi; Fitricia Andreani (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Academic achievement among elementary school children is influenced by various factors, including nutritional status, diet quality, and nutrition knowledge. These factors play a crucial role in supporting cognitive development and learning performance. This study aimed to analyze the association between diet quality, nutritional status, and nutrition knowledge as predictors of academic achievement among elementary school children. A cross-sectional design was employed, involving 60 students selected using simple random sampling. Nutritional status was assessed using body mass index-for-age (BMI/A), diet quality was evaluated using a diet quality index score (range 0–100), and nutrition knowledge was measured using a standardized questionnaire. Data were analyzed using SPSS version 26. The Kolmogorov–Smirnov test was performed to confirm normality before conducting Pearson correlation and multiple linear regression analyses. The results showed significant correlations between academic achievement and diet quality (r = 0.42; p = 0.0012), nutritional status (r = 0.36; p = 0.0045), and nutrition knowledge (r = 0.28; p = 0.0321). Multiple regression analysis revealed that all three variables were significant predictors of academic achievement, with R² = 0.42 and adjusted R² = 0.39, indicating that 39% of the variance in academic achievement was explained by these predictors. In conclusion, diet quality, nutritional status, and nutrition knowledge contribute significantly to improving academic achievement among elementary school children.